Pre-shock chest compression pause effects on termination of ventricular fibrillation/tachycardia and return of organized rhythm within mechanical and manual cardiopulmonary resuscitation. (August 2015) - Olsen, Jan-Aage; Brunborg, Cathrine; Steinberg, Mikkel; Persse, David; Sterz, Fritz; Lozano, Michael; Westfall, Mark; Travis, David T.; Lerner, E. Brooke; Brouwer, Marc A.; Wik, Lars
Abstract: Background: Shorter manual chest compression pauses prior to defibrillation attempts is reported to improve the defibrillation success rate. Mechanical load-distributing band (LDB-) CPR enables shocks without compression pause. We studied pre-shock pause and termination of ventricular fibrillation/pulseless ventricular tachycardia 5 s post-shock (TOF) and return of organized rhythm (ROOR) with LDB and manual (M-) CPR. Methods: In a secondary analysis from the Circulation Improving Resuscitation Care trial, patients with initial shockable rhythm and interpretable post-shock rhythms were included. Pre-shock rhythm, pause duration (if any), and post-shock rhythm were obtained for each shock. Associations between TOF/ROOR and pre-shock pause duration, including no pause shocks with LDB-CPR, were analyzed with Chi-square test. A p -value <0.05 was considered statistically significant. Results: For TOF and ROOR analyses we included 417 LDB-CPR patients with 1476 and 1438 shocks, and 495 M-CPR patients with 1839 and 1796 shocks, respectively. For first shocks with LDB-CPR, pre-shock pause was associated with TOF ( p  = 0.049) with lowest TOF (77%) for shocks given without pre-shock compression pause. This association was not significant when all shocks were included ( p  = 0.07) and not for ROOR. With M-CPR there were no significant associations between shock-related chest compression pause duration and TOF or ROOR. Conclusion: For first shocks with LDB-CPR, termination of fibrillation was associated with pre-shock pause duration. There was no association for the rate of return of organized rhythm. For M-CPR, where no shocks were given during continuous chest compressions, there were no associations between pre-shock pause duration and TOF or ROOR.